Review of Bank Syariah Indonesia (BSI) Brand Image at BSI KCP Tanjungsari - Aldina Desy Fajriyanti; Widya Sastika (Fakultas Ekonomi Universitas Garut, 2024)
The economic growth rate of Indonesia is anticipated to reach 5.05% by 2023, reflecting strong momentum in the business sector. Banks play a crucial role in financing, resource allocation, and economic development through financial products and digital services, such as mobile banking. As the Islamic banking sector continues to grow rapidly, its assets are expected to surpass Rp 831.95 trillion, with a market share reaching 7.09% by 2023, making brand image a vital factor in building customer trust. This study examines the brand image of Bank Syariah Indonesia (BSI) at BSI KCP Sumedang Tanjungsari 2, following a customer data leak in May 2023 that caused service disruptions and customer dissatisfaction. The aim of this study is to assess the brand image of BSI KCP Sumedang Tanjungsari 2, identify factors influencing it, and pinpoint areas for improvement. The analysis reveals that BSI KCP Sumedang Tanjungsari 2 maintains a strong brand image, as perceived by customers, due to its strength, direction, and uniqueness.The brand's strength is linked to the trust in employee reliability, while brand integrity is demonstrated by the brand's memorability and excellent service. Additionally, the brand's uniqueness is found in its Shariah-based services, which differentiate it from conventional banks. Through a quantitative approach with a descriptive analysis, this study concludes that a positive brand image contributes to the growth of Islamic banking.